The Development of Pesantren Patterns in Sidosermo Surabaya: Integrating tradition and modernity - Kurniadi, Kurniadi; Chotib, Moch.; Khumaidah, Sofkhatin; Kumaini, Ruston; Harisi, Isnain La (el Harakah: Jurnal Budaya Islam, 2025)
Islamic boarding schools in Indonesia, as traditional Islamic educational institutions, have undergone significant transformations in recent decades. Adopting a modern curriculum is important to ensure that pesantren students have skills that are relevant to the times. By integrating religious and general sciences, pesantren can produce graduates who not only have a strong Islamic understanding, but are also competitive in the world of work. While existing studies have explored the integration of modern subjects into pesantren curricula in several regions, there remains a research gap concerning how this integration unfolds in East Java, where distinct cultural and regional dynamics influence educational practices. Therefore, this research aims at analysing the development patterns of pesantren in Indonesia in a case study of the Sidosermo Pesantren Area in Surabaya by highlighting how they integrate deeply rooted traditions with the demands of modernity. Using a qualitative approach, this study collected data through in-depth interviews, participatory observation, and literature study. The results revealed that the pesantren managed to maintain traditional values, such as the teaching of the yellow book and grave pilgrimage, while adopting modern elements that include formal curriculum, digital technology, and professional-based management. This integration process not only strengthens the role of pesantren as centers of religious education, but also places them as agents of social change that are responsive to the challenges of the times. Nevertheless, pesantren are faced with a great challenge in maintaining a balance between maintaining tradition and innovating. This study demonstrates that the success of pesantren in facing modernity depends on their ability to hold on to fundamental Islamic values, open to global developments and information technology today. The recommendations include developing a hybrid curriculum combining religion, science, and technology; integrating e-learning tools; promoting pesantren-based economic initiatives; and strengthening alumni networks to support institutional growth and student careers. Pondok pesantren di Indonesia, sebagai lembaga pendidikan Islam tradisional, telah mengalami transformasi yang signifikan dalam beberapa dekade terakhir. Penerapan kurikulum modern menjadi penting untuk memastikan bahwa para santri memiliki keterampilan yang relevan dengan perkembangan zaman. Dengan mengintegrasikan ilmu agama dan ilmu umum, pesantren dapat menghasilkan lulusan yang tidak hanya memiliki pemahaman Islam yang kuat, tetapi juga mampu bersaing di dunia kerja. Meskipun studi sebelumnya telah meneliti integrasi mata pelajaran modern dalam kurikulum pesantren di beberapa daerah, masih terdapat kesenjangan penelitian mengenai bagaimana integrasi tersebut berlangsung di Jawa Timur, di mana dinamika budaya dan regional yang khas memengaruhi praktik pendidikan. Oleh karena itu, penelitian ini bertujuan untuk menganalisis pola pengembangan pesantren di Indonesia melalui studi kasus di Kawasan Pesantren Sidosermo Surabaya, dengan menyoroti bagaimana mereka mengintegrasikan tradisi yang mengakar kuat dengan tuntutan modernitas. Dengan pendekatan kualitatif, penelitian ini mengumpulkan data melalui wawancara mendalam, observasi partisipatif, dan studi pustaka. Hasil penelitian menunjukkan bahwa pesantren berhasil mempertahankan nilai-nilai tradisional, seperti pengajaran kitab kuning dan ziarah makam, sekaligus mengadopsi elemen-elemen modern yang mencakup kurikulum formal, teknologi digital, dan manajemen berbasis profesional. Proses integrasi ini tidak hanya memperkuat peran pesantren sebagai pusat pendidikan agama, tetapi juga menempatkan mereka sebagai agen perubahan sosial yang responsif terhadap tantangan zaman. Namun demikian, pesantren dihadapkan pada tantangan besar dalam menjaga keseimbangan antara pelestarian tradisi dan inovasi. Studi ini menunjukkan bahwa keberhasilan pesantren dalam menghadapi modernitas bergantung pada kemampuan mereka untuk berpegang pada nilai-nilai dasar Islam, terbuka terhadap perkembangan global dan teknologi informasi saat ini. Rekomendasi dari penelitian ini mencakup pengembangan kurikulum hibrida yang menggabungkan agama, sains, dan teknologi; integrasi perangkat e-learning; penguatan inisiatif ekonomi berbasis pesantren; serta penguatan jaringan alumni untuk mendukung pertumbuhan kelembagaan dan karier santri.